CUSTOMER SATISFACTION MEDIATES THE EFFECT OF SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER LOYALTY - Andriasan Sudarso; Lili Suryati; Lenny Menara Sari Saragih; Maretta Ginting; Wikrama Wardana; Lenggogeni Lenggogeni; Rita Zahara (Universitas Padjadjaran, 2023)
The purpose of this research is to investigate the ways in which features of a business’s operations, such as the level of service quality and the value it gives to consumers, may have a direct influence on the degree to which customers are satisfied with the company and remain loyal to the organization. In this investigation, the technique for evaluating the data is called structural equation modeling partial squares (SEM-PLS), and the application that was used is called Warp PLS. Both of these terms relate to the same thing: the evaluation method for the data. One hundred persons, in all, took part in the inquiry that was being conducted. According to the findings, there was a significant and obvious correlation between the quality of service that was provided to customers and the value that they got in terms of customer satisfaction as well as customer loyalty. This was the case even though there was no direct causal relationship between the two variables. In addition, there is a connection between happy customers and a successful firm. The service that they got by looking at the value that was supplied to the customer.